Strategi penguatan pendidikan luar sekolah - Maulani, Kharisma (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze various strategies for strengthening non-formal education as an effort to enhance the role of community-based learning institutions in promoting equitable access and social empowerment. Non-formal education serves as an alternative learning space that is flexible, inclusive, and contextually relevant for communities beyond the reach of formal education systems. This research employs a qualitative approach using a literature review method focused on synthesizing academic sources related to institutional management, educator professionalism, digital learning innovation, community empowerment, and non-formal education policy. The findings indicate that strategies to strengthen non-formal education include institutional capacity development, improvement of educator quality, educational technology innovation, cross-sector partnerships, and government regulatory support. The synergy of these five aspects is essential in building adaptive and collaborative non-formal education institutions oriented toward lifelong learning. The study concludes that strengthening non-formal education is not merely a technical process but a strategic endeavor to drive social transformation and sustainable human development.